2022
DOI: 10.1155/2022/2605592
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors of Benign Stricture of Anastomotic Stoma after Esophagectomy and Therapeutic Effect of Stent Implantation

Abstract: With the increase in the number of patients and prolongation of their lives after esophagectomy for esophageal cancer, the quality of life after surgery has attracted more and more attention. Although anastomotic stenosis is a common complication, it seriously affects the quality of life and psychological state of patients or even threatens their lives. At present, the exact independent influencing factors of anastomotic stenosis after esophageal cancer surgery have not been determined, and relevant treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Owing to continuous expansion, Martin et al successfully used RSEMS to treat refractory anastomotic strictures with lower cost and more e ciency [22]. Stent implantation for BEAS is safe and has several advantages [37]. Endoscopic stent placement also had a comparative effect with endoscopic incision for esophageal anastomotic stricture [38].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to continuous expansion, Martin et al successfully used RSEMS to treat refractory anastomotic strictures with lower cost and more e ciency [22]. Stent implantation for BEAS is safe and has several advantages [37]. Endoscopic stent placement also had a comparative effect with endoscopic incision for esophageal anastomotic stricture [38].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to continuous expansion, Martin et al successfully used RSEMS to treat refractory anastomotic strictures with lower cost and more e ciency [22]. Stent implantation for BEAS is safe and has several advantages [37].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%